2007
DOI: 10.1021/tx700102n
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Acrolein-Glycerophosphoethanolamine Lipid Adducts Using Electrospray Mass Spectrometry

Abstract: Acrolein is a toxic, highly reactive α,β-unsaturated aldehyde. In the current study, the products of acrolein after reaction with glycerophosphoethanolamine (GPEtn) lipids have been characterized using electrospray tandem mass spectrometry. The major product formed involves the addition of two acrolein molecules to the primary amine of GPEtn lipids and subsequent aldol condensation to form 1,2-diradyl-sn-glycero-3-phosphoethanol-(3-formyl-4-hydroxy)piperidine (FHP) lipids. Upon sodium borohydride reduction, 1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 46 publications
0
22
0
Order By: Relevance
“…The time course revealed that the addition of acrolein at the same time as GM-CSF (-30 min) did not have any effect on 5-LO product formation compared to the GM-CSF/fMLP treated neutrophils with no acrolein added. From previous studies, it was found that acrolein (≤30 μM) rapidly disappears as soon as 3 min after being added to cells (10). Therefore, no acrolein remained when fMLP was added after the 30 min of incubation of human neutrophils with GM-CSF and acrolein.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The time course revealed that the addition of acrolein at the same time as GM-CSF (-30 min) did not have any effect on 5-LO product formation compared to the GM-CSF/fMLP treated neutrophils with no acrolein added. From previous studies, it was found that acrolein (≤30 μM) rapidly disappears as soon as 3 min after being added to cells (10). Therefore, no acrolein remained when fMLP was added after the 30 min of incubation of human neutrophils with GM-CSF and acrolein.…”
Section: Resultsmentioning
confidence: 99%
“…While these estimates are based upon model systems, it is clear that acrolein can be present in very high concentrations exposed to cells as well as fluids in the lung. Acrolein is also known to be highly reactive for proteins (6) and lipids (10), resulting in the covalent binding of acrolein either through Schiff base or Michael addition reactions to target molecules. It has been suggested that such adducts may play an important role in the toxicity of acrolein.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its reaction with the thiol groups of cysteine, acrolein reacts with the imidazole group of histidine and with primary amines, but at a much slower rate [5]. Acrolein can also slowly react with the guanidine group of arginine and of guanosine [21, 24]. Reaction of acrolein with primary amines forms an Nε-(3-formyl-3,4-dehydropiperidino) adduct (FDP) [25] while reaction with arginine and nucleic acids forms cyclic hydroxyl- N -propano adducts [5] (Table 1).…”
Section: Properties Of Individual Reactive Carbonyls Speciesmentioning
confidence: 99%
“…The compound was further cyclized under aldol condensation to form Nα -acetyl-Nε-(3-methylpyridinium)lysine N -MP-Lys or N ε-(3-formyl-3,4-dehydropiperidino)lysine ( N -FDP-Lys) (Furuhata et al, 2003; Uchida et al, 1998) (Fig 18). Berry and Murphy investigated acrolein reactions with PE and they found only N -FDP-PE and not the imine adduct or its secondary product N -MP-PE (Zemski Berry and Murphy, 2007). Of course, this does not exclude the possibility that such adducts might form under different conditions.…”
Section: Class Iv: Oxidatively N-modified Phospholipids (Pl)mentioning
confidence: 99%
“…Based on the reaction of acrolein with lysine, it was expected that the reaction of acrolein with PE would generate both N-(3-methylpyridinium)-PE ( N -MP-PE) and N -(3-formyl-3,4-dehydropiperidino)-PE ( N -FDP-PE) (Furuhata et al, 2003; Uchida et al, 1998). However, only formation N-FDP-PE has been detected in vitro (Zemski Berry and Murphy, 2007). …”
Section: Figurementioning
confidence: 99%